Case Report: The molecular fingerprint and the clinical implication of an exceptional response to neoadjuvant therapy in a metastatic cardia adenocarcinoma - Lorenzon, Laura; Campisi, Andrea; Di Paolo, Alessandra; Giuliante, Felice; Buttitta, Fiamma; D’Ugo, Domenico (Frontiers in Surgery, 2024)
Background: Globally, gastric cancer holds the fi`h posi]on in terms of prevalence among malignant tumors and is the fourth leading cause of cancer-related mortality. Par]cular aaen]on should be paid to cardia adenocarcinoma (CA) due to its increasing incidence and poor prognosis.Diagnosis of CA frequently occurs in advanced stage because of its late symptoms. In such cases, neoadjuvant chemotherapy is the primary treatment op]on. The response to chemotherapy depends on mul]ple variables including the tumor's molecular profile, pa]ent's performance status, and the feasibility of using targeted therapy. Pa]ents exhibi]ng an excep]onal response, defined as a complete response to medical therapy las]ng more than one year, or a par]al response or stable disease las]ng more than two years, are rarely described. This case report presents one of the longest-las]ng excep]onal responses to chemotherapy in metasta]c cardia adenocarcinoma and discusses its clinical implica]ons.A 49-year-old male pa]ent presented with cardia adenocarcinoma (HER2 nega]ve, MMR proficient) and liver metastases. Molecular profiling iden]fied a pathogenic muta]on in the TP53 gene (R123W; Arg123Trp) as the sole altera]on found. Five months a`er ini]a]ng the neoadjuvant chemotherapy with Flurouracil-Leucovorin-Oxalipla]n-Docetaxel, the pa]ent achieved a complete clinical response. The molecular profile was compared to others previously documented in an interna]onal data portal, revealing a similar paaern.At four years and three months from diagnosis, the excep]onal response was s]ll confirmed.The pa]ent underwent a cumula]ve number of thirty-three cycles of chemotherapy, leading to chemotherapy induced liver damage.Excep]onal responses to neoadiuvant chemotherapy in cardia adenocarcinomas are rarely reported. The documenta]on of excep]onal responses to cancer therapies should be included in large data repositories to explore the molecular fingerprint of these tumors. In such cases, the clinical implica]ons of long-term chemotherapy should always be taken into account.